Hubungan Dukungan Suami Terhadap Tingkat Kecemasan Ibu Hamil Primigravida Dalam Menghadapi Persalinan di Klinik Permana - sintya agustini; Komang Srititin Agustina (Universitas Triatma Mulya, 2022)
Introduction. Pregnancy in general gives a very big emotional meaning to every woman. As a married woman, childbirth is the most awaited period. Feelings of happiness as well as anxiety are inevitable events, almost all pregnant women are overshadowed by anxiety, and part of a natural adjustment process to the psychological changes that occur during pregnancy. 15,000 of the approximately 4.5 million women giving birth state that they feel fear and anxiety. Support from husbands is needed by pregnant women especially at the age of pregnancy entering the third trimester which is approaching the time of delivery in order to reduce excess anxiety. Methods: This study uses a quantitative research type with an analytic survey research design and a cross-sectional approach. The population in this study were primigravida pregnant women as many as 30 respondents and the sample in this study used purposive sampling. Data analysis was performed using the Pearson Chi-square statistical test. Results: statistical test obtained a value of p = 0.001 with a degree of significance (α = 0.05), so it was found that p <α, meaning that Ha is accepted, meaning that there is a relationship between husband's support and the level of anxiety of primigravida pregnant women in facing childbirth at the Permana Clinic. Conclusion: there is a relationship between husband's support and the anxiety level of primigravida pregnant women in dealing with childbirth at the Permana Clinic.